Construction of Local Drug Delivery System on Titanium-Based Implants to Improve Osseointegration - Fanying Meng; Zhifeng Yin; Xiaoxiang Ren; Zhen Geng; Jiacan Su (MDPI AG, 2022)
Titanium and its alloys are the most widely applied orthopedic and dental implant materials due to their high biocompatibility, superior corrosion resistance, and outstanding mechanical properties. However, the lack of superior osseointegration remains the main obstacle to successful implantation. Previous traditional surface modification methods of titanium-based implants cannot fully meet the clinical needs of osseointegration. The construction of local drug delivery systems (e.g., antimicrobial drug delivery systems, anti-bone resorption drug delivery systems, etc.) on titanium-based implants has been proved to be an effective strategy to improve osseointegration. Meanwhile, these drug delivery systems can also be combined with traditional surface modification methods, such as anodic oxidation, acid etching, surface coating technology, etc., to achieve desirable and enhanced osseointegration. In this paper, we review the research progress of different local drug delivery systems using titanium-based implants and provide a theoretical basis for further research on drug delivery systems to promote bone-implant integration in the future.